Building social capital in French "Poles d'Excellence Rurale": the "rural excellency" as a modus vivendi for rural development - Ion Lucian Ceapraz (European Regional Science Association (ERSA), 2011)
Our paper emphasizes the role of social capital in French "Poles d'Excellence Rurale (PER). Social capital is considered as highly valuable when considering the development of these particular rural areas. More precisely the French "Poles d'Excellence Rurale" are the perfect example of application of norms and networks that enable collective action and thus create social capital. These PER are functioning on traditional activities and social forms of organization which enables them to be competitive on a specific territory. We propose to develop and interrogate the role of two concepts already described as the major functional mechanism of a PER: a) the "rural excellency" and the "territorial engineering" (Lardon, Pin, 2007) which form one and a single concept related to the spatial diffusion of economic, social and organizational innovation through territorial competition and, b) the concept of "private-public partnership" , a management project developed by several actors able to develop and use various kinds of social networks. In the first case, the "rural excellency" characterizes the functional core of a PER and is related to the "diffusing effect" of specific comparative advantages of economic and social nature. We mention here the governance as one type of "rural excellency" which allows governments to "outsource" some of its welfare functions to local rural communities (Bifarello, 2002). Thus this process is supposed to initiate a competition between different rural territories followed by a selection among the "best territorial engineered territories" within the process of "territorial engineering". In the second case, the "private-public partnership" of a PER implies a bottom-up policy involving local communities and actors with a certain democratic legitimacy (Trouvé, 2009) and thus supporting partnerships between local actors somehow in opposition with government "top-down" policies. Our methodology is based on the report entitled "Facteurs de localisation et gouvernance dans les Poles d'Excellence Rurale" developed by CAESAR-AgroSup Dijon, (2009) which emphasize the type of partnership between different actors depending on different "request for proposals" and "expected rural spillovers" for each type of PER.
Keywords: 330